2006
DOI: 10.1194/jlr.c600003-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

SRp30a (ASF/SF2) regulates the alternative splicing of caspase-9 pre-mRNA and is required for ceramide-responsiveness

Abstract: Two splice variants are derived from the caspase-9 gene, proapoptotic caspase-9a and antiapoptotic caspase9b, by either the inclusion or exclusion of an exon 3, 4, 5, and 6 cassette. Previous studies from our laboratory have shown that the alternative splicing of caspase-9 and the phosphorylation status of SR proteins, a conserved family of splicing factors, are regulated by chemotherapy and ceramide via the action of protein phosphatase-1. In this study, a link between ceramide, SR proteins, and the alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 40 publications
(37 reference statements)
5
73
0
Order By: Relevance
“…For example, SRp30a (SRSF1) was shown to be a proto-oncogene and up-regulated in a large percentage of breast cancers (39 -41). This factor has also been shown to be hyperphosphorylated in lung cancer cells, which is linked to the alternative splicing of caspase 9 and cancer phenotypes such as anchorageindependent growth, chemotherapy resistance, and tumor formation (42,43). The expression of a number of RNA splicing factors is also linked to tumor progression in various cancers and cancer phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SRp30a (SRSF1) was shown to be a proto-oncogene and up-regulated in a large percentage of breast cancers (39 -41). This factor has also been shown to be hyperphosphorylated in lung cancer cells, which is linked to the alternative splicing of caspase 9 and cancer phenotypes such as anchorageindependent growth, chemotherapy resistance, and tumor formation (42,43). The expression of a number of RNA splicing factors is also linked to tumor progression in various cancers and cancer phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The splicing regulatory activity of ASF/ SF2 depends on its phosphorylation status, and the sphingolipid metabolite D-erythro-C 6 -ceramide is shown to modulate the splicing activity of ASF/SF2 through a protein phosphatase 1-mediated dephosphorylation of ASF/SF2 (19). We treated T cells with increasing concentrations of ceramide and assessed its effect on CD3 UTR alternative splicing by reverse transcription (RT)-PCR.…”
Section: Asf/sf2 Represses Alternative Splicing Of the Exon Viii-defimentioning
confidence: 99%
“…[15][16] The inclusion or exclusion of an exon cassette in caspase-9 causes the expression of two splice variants, namely the pro-apoptotic caspase-9a and antiapoptotic caspase-9b. [17][18] To assess whether E2F1 induces changes in the alternative splicing profile of these caspases pre-mRNAs, RNAs recovered from non-induced or induced H358/Tet-On/E2F1 cells were analyzed by RT-PCR using primers specific for each caspase splice variant (Figure 4a). The results showed that E2F1 increased the expression of pro-apoptotic caspases-2L, -8a and -9a mRNA levels and decreased those of anti-apoptotic caspases-8L and -9b (Figure 4b).…”
Section: Wild-type E2f1 -/-mentioning
confidence: 99%